Povidone-Iodine Fails to Eradicate Chronic Suppurative Otitis Media and Demonstrates Ototoxic Risk in Mice. Issue 10 (14th December 2022) - Kaufman, Adam C.; Bacacao, Brian S.; Berkay, Betul; Sharma, Devesh; Mishra, Anupam; O'Toole, George A.; Saunders, James E.; Xia, Anping; Bekale, Laurent A.; Santa Maria, Peter L.
Abstract : Hypothesis: Commercially available povidone-iodine solution can eliminate biofilms and persister cells rapidly in in vivo achievable concentrations without inducing ototoxicity. Background: Chronic suppurative otitis media (CSOM) is a substantial global problem. Current treatment options often induce a temporary remission without leading to a permanent cessation of symptoms secondary to the treatments' inability to eliminate persister cells. Povidone-iodine has been shown to be able to clear biofilm and planktonic cells in in vitro assays, but there are reports of ototoxic effects limiting its clinical utility. Methods: Bacterial and biofilm growth with quantification by spectrophotomer, murine auditory brainstem response (ABR), and distortion product otoacoustic emissions, immunohistochemistry, in vivo povidone-iodine treatment of murine CSOM, persister cell assay. Results: Commercially available 10% povidone-iodine solution is able to completely eradicate multiple clinical strains of Pseudomonas aeruginosa and Staphylococcus aureus in vitro with 10 minutes of exposure. Mice that have received a transtympanic injection of 1% povidone-iodine solution did not have significantly different auditory brainstem response or distortion product otoacoustic emission results compared with the control. Mice that received a povidone-iodine scrub or 10% povidone-iodine solution had significantly worsened hearing (25- and 13-dB increase in threshold, respectively; p < 0.05). In vivo CSOM infection recurred in all mice after the completion of treatment with 10% povidone-iodine solution, and there was no improvement in the bacterial load after treatment, indicating in vivo failure of therapy. Conclusion: Povidone-iodine solution is effective at eliminating biofilm and persister cells in vitro at in vivo achievable concentrations but fails in vivo most likely because of kinetics of distribution in vivo. Even if drug distribution could be improved, the therapeutic window is likely to be too small given that the diluted solution does not have ototoxic potential, whereas while the scrub variant, which contains detergents, and the undiluted solution are ototoxic after a single treatment.